A blistering new era for bullous pemphigoid: A scoping review of current therapies, ongoing clinical trials, and future directions. (October 2021) - Khalid, Subaina Naeem; Khan, Zeest Ali; Ali, Muhammad Hamza; Almas, Talal; Khedro, Tarek; Raj Nagarajan, Vikneswaran
Abstract: Bullous pemphigoid (BP) is a severe autoimmune blistering skin disorder that primarily causes disease in the older population and is the most prevalent subepidermal variant of the pemphigoid diseases. It manifests as exquisitely pruritic vesiculobullous eruptions and is associated with significant morbidity and mortality. Studies are reporting an increase in prevalence, and, among the elderly, BP is no longer considered to be as rare as previously thought. The pathogenesis involves autoantibodies directed against proteinaceous components of hemidesmosomes, with consequent autoimmune destruction of the dermal-epidermal junction. In recent times, more complex elements of the underlying inflammatory orchestra have been elucidated and are being used to develop targeted immunotherapies. The primary treatment modalities of BP include the use of topical and systemic corticosteroids, certain non-immunosuppressive agents (tetracyclines, nicotinamide, and sulfone), and immunosuppressants (methotrexate, azathioprine, cyclophosphamide, and Mycophenolate). However, in the long term, most of these agents are associated with substantial toxicities while recurrence rates remain high. Such egregious prospects led to significant efforts being directed towards developing newer targeted therapies which work by attenuating specific newly discovered pillars of the inflammatory pathway, and these efforts have garnered hope in providing safer alternatives. Our review focuses on presenting the various therapeutic options that are currently in trial since December 2019, as well as on summarizing presently established treatment guidelines to provide readers with the latest exciting updates. Highlights: Bullous pemphigoid (BP) is a severe autoimmune blistering skin disorder that primarily causes disease in the older population and is the most prevalent subepidermal variant of the pemphigoid diseases. In recent times, more complex elements of the underlying inflammatory orchestra have been elucidated and are being used to develop targeted immunotherapies. The present review focuses on presenting the various therapeutic options that are currently in trial since December 2019, as well as on summarizing presently established treatment guidelines to provide readers with the latest exciting updates.